Monotonic and cyclic response of bolted connections with welded cover plate for modular steel construction. (15th July 2018) - Deng, En-Feng; Zong, Liang; Ding, Yang; Dai, Xiao-Meng; Lou, Ni; Chen, Yang
Highlights: An architecturally pleasing connection for modular steel construction was proposed. Seven full-scaled specimens were tested under monotonic and cyclic load. Load-transferring mechanism and seismic performance were evaluated and discussed. The proposed design formula predicts well the bending capacity of the connection. Abstract: Attributable to the superiority in construction speed and quality, modular steel constructions (MSCs) have been increasingly used for mid-to-high rise buildings with repetitive units. An architecturally pleasing bolted connection with welded cover plate was proposed in this paper to settle the current research limit. Tests on seven full-scaled tee-shape connections made of hollow structural section (HSS) members were conducted under monotonic and cyclic load. The results indicated that all the specimens under monotonic load were capable of developing the full plastic strength of the twin-beams. The twin-beams were found to have individual bending behavior. The current seismic design code GB 50011-2010 and AISC 341-10 were used to evaluate the seismic performance and verify the applicability for seismic design of the proposed connection, demonstrating the satisfactory deformation capacity and ductility. Furthermore, EC3 Part 1–8 was adopted to evaluate the stiffness characteristic of the proposed connection, indicating that the proposed connection can be classified as "semi-rigid" connection. In addition, the design consideration was recommended to predict the bending capacity of the proposed connection. The presented research work will provide useful references for expanding the application of MSCs.